THE FINANCIAL MANAGEMENT PRACTICES OF STATE MOSQUES IN PENINSULAR MALAYSIA - Siti Alawiah Siraj; Shahul Hameed Mohamed Ibrahim; Maliah Sulaiman (Universitas Trisakti, 2007)
Scandals involving fraud and embezzlement of significant amounts of the financial resources of Western Church Institutions are increasingly becoming more common. Such scandals have raised concerns as to the ability of internal control systems within the organizations to restrict such occurrences. Although, no such scandals have been reported for Islamic organizations, to date (particularly mosques), there is concern as to whether these organizations experience the same deficiencies as the Western church institutions. As such, the study examines the existing financial management practices of state mosques in Peninsular Malaysia, particularly in the areas of budgeting, receipts of income, disbursement of funds and reporting. A questionnaire survey and face-to-face interviews were employed in collecting the data. The results of the study indicate that state mosques in Peninsular Malaysia have a strong internal control system pertaining to the receipt of income and disbursements of funds. However, state mosques are still lacking in budgetary and reporting controls. The study also reveals that basic control activities such as the segregation of duties, recording of financial transactions and authorization of particular activities are satisfactorily practiced within the state mosques. Although this is an exploratory study, the results may provide a benchmark for further studies in the financial management practices of Islamic organizations in Malaysia. Key Terms : Islamic Accounting. Mosque accounting. Mosque internal controls Malaysia Mosque